ANALYSIS OF POOR FAMILIES WELFARE AND POVERTY REDUCTION STRATEGIES IN TIMOR-LESTE - Soares L.; Utama I M.S.; Yuliarmi N.N.; Yasa I N.M. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
Poverty is often cited as the main problem experienced by developing countries, and Timor-Leste is no exception. Timor-Leste is a country that is still struggling with poverty. This indicates that poverty alleviation programs must continue to be promoted to create sustainable community welfare. Efforts and cooperation of various parties are needed to find ways for the community to get out of poverty and realize the welfare they want. This research aims to obtain an in-depth picture of low-income families' welfare and study poverty reduction strategies in Timor-Leste. The research method used in this study is a literature review. The results show that there are still many poor families in Timor-Leste, and the unequal distribution of public facilities and infrastructure in each district in Timor-Leste indicates that family welfare has not been fully realized. The poverty alleviation strategies that the Government can implement can be divided into two major parts, namely first protecting families and community groups that experience temporary poverty, and second helping people who experience chronic poverty by empowering and preventing new poverty. The strategy is then outlined in three programs that are directly directed at the poor, namely: (1) provision of basic needs; (2) development of a social security system, and (3) development of a business culture.